Feedback control of dynamic systems / Gene F Franklin; J David Powell; Abbas Emami-Naeini - Franklin, Gene F.
Feedback Control of Dynamic Systems, 8th Edition, covers the material that every engineer needs to know about feedback control―including concepts like stability, tracking, and robustness. Each chapter presents the fundamentals along with comprehensive, worked-out examples, all within a real-world context and with historical background provided. The text is devoted to supporting readers equally in their need to grasp both traditional and more modern topics of digital control, and the author focuses on design as a theme early on, rather than focusing on analysis first and incorporating design much later. An entire chapter is devoted to comprehensive case studies, and the 8th Edition has been revised with up-to-date information, along with brand-new sections, problems, and examples.